Indexes to Debates of the House of Assembly (Hansard) - South Africa Parliament, House of Assembly (Cape Town Government Printers, 1992)
South Africa Debates of Parliament (Hansard).
South Africa Politics and government. Formed by a merger of: Debates of the House of Assembly, Debates of the House of Delegates, and Debates of the House of Representatives. 22 cm.
Keywords: Indexes to Debates; Parliament; Hansard; Fourth Session; Ninth Parliament; 22 January; 21 October; 1992; Vol. 37; ISBN 0621148377; ISBN 0621148385; JC263118; Index to Speeches; House of Assembly; House of Delegates; House of Representatives